The effects of risk and ambiguity aversion on technology adoption: Evidence from aquaculture in Ghana - Christian Crentsil; Adelina Gschwandtner; Zaki Wahhaj (University of Kent, School of Economics, 2018)
We study how aversion to risk and ambiguity affects the adoption of new technologies by Ghanaian smallholder aquafarmers. We conduct a set of field experiments designed to elicit farmers' risk and ambiguity preferences and combine it with surveybased information on their technology adoption decisions. We find that aquafarmers who are more risk-averse were quicker to adopt the new technologies: a fast-growing breed of tilapia fish, extruded feed and floating cages. By contrast, ambiguity aversion has no effect on the adoption of the new tilapia breed and extruded feed. Furthermore, it slows down the adoption of floating cages - a technology which entails higher fixed costs than the others - and the effect is diminishing in the number of other adopters in the village. We argue that these differential effects are due to the fact that the technologies are risk-reducing, with potential ambiguity about their payoff distributions at the early stages of adoption. The findings highlight the importance of distinguishing between risk and ambiguity in investigating technology adoption decisions of small-holder farmers in developing countries.
Keywords: C93; D81; O33; Q12; Q16; 330; Uncertainty Aversion; Aquafarming; Technology Adoption; Extruded Feed; Floating Cages; Akosombo strain of Tilapia (AST)